Evaluation of hormonal profile and some stress biomarkers in infertile couples in Abuja, Nigeria - Abriba, Simon P.; Osadolor, Humphrey B. (International Journal of Research in Medical Sciences, 2020)
Background: Infertility is a growing gynaecological problem in couples of childbearing age having difficulties bearing children. Couples with infertility are known to present with high levels of stress and psychopathology A cross sectional case control study aimed at evaluating the hormonal profile, some stress biomarkers, sperm analysis in infertile couples was carried out to ascertain their contributions to infertility in couples of child bearing age. Methods: Serum Luteinizing Hormone (LH), Follicle Stimulating Hormone (FSH), Prolactin, Progesterone, Estrogen (E2), Testosterone, Salivary Cortisol and Salivary Alpha Amylase were evaluated using both competitive and non-competitive Enzyme Linked Immunosorbent Assay (ELISA) techniques; while sperm cells analysis were evaluated using conventional methods, in 164 infertile couples (study) and 100 fertile couples (control) attending fertility clinic in General Hospitals in Abuja, Nigeria. Results: The mean serum Prolactin and Salivary (S) Cortisol in the female were significantly higher (p<0.05) in the study group relative to the control group, while Salivary Alpha Amylase and LH show no significant difference (p>0.05) between the two groups. FSH, Progesterone and E2 in the female were significantly lower in the study group (p<0.05) compared with control group. Testosterone, FSH, Sperm cells count and Sperm activity (%) were significantly lower (p<0.05) in the male study group relative to the control group; while prolactin, S. cortisol and S. amylase were significantly higher (p<0.05) in the male study group relative to the control group. Conclusions: Abnormal hormones values and abnormal sperm quality and quantity are associated with elevated stress biomarkers in couples presenting with infertility. Strong positive correlations exist between hormones and stress biomarker in infertility conditions.